2023
DOI: 10.1101/2022.12.31.22284080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cannabis-Microbiome Interactions in Varied Clinical Contexts: A Comprehensive Systematic Review

Abstract: Background: Cannabis is being legalized in many countries for therapeutic and recreational purposes. The cannabinoid compounds are mainly involved in the host metabolism under the endocannabinoid system, and they regulate the intestinal microbiota via an immunomodulatory mechanism leading to obtaining positive effects on the gastrointestinal and immunological systems. Objective: The review is to systematically evaluate their association and the impact of the microbiome on cannabis treatment to support further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Early studies have shown that cannabinoids may alleviate intestinal inflammation in experimental IBD models. These properties of cannabis contribute to the interest in exploring a therapeutic role for it in IBD [ 7 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have shown that cannabinoids may alleviate intestinal inflammation in experimental IBD models. These properties of cannabis contribute to the interest in exploring a therapeutic role for it in IBD [ 7 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, different cannabis variety may contain different numbers and amounts of bioactive compounds, potentially leading to different effects ( 81 , 82 ). A systematic review and meta-analysis has also found inconsistent results regarding cannabis’ impact on the gut microbiome across studies, highlighting the need for more comprehensive research to decipher the precise mechanisms and consequences of cannabis on gut microbiota ( 83 ). Furthermore, cannabis consumption has demonstrated potential benefits in ulcerative colitis patients, such as altering endocannabinoid tone and inducing mucosal healing, but the involvement of gut microbiota in these effects remains unclear ( 84 ).…”
Section: Lifestylementioning
confidence: 99%